The Portrait of Traditional Islamic Education System in Indonesia - Kurniawan, Dadan Adi (Sebelas Maret University (UNS), 2019)
In its history, the traces of the development of education in Indonesia have various variants, systems and patterns. One of them is traditional Islamic education. The entry of Islam into Indonesia has given its own color and style to the national education system, in addition to pre-academic, Hindu-Buddhist, Dutch and Japanese colonial education. In Islamic education there is a system of work on how education is run. This paper aims to : (1) know what is the Islamic education, (2) research more how is the portrait of the traditional Islamic education system in Indonesia, and (3) as well as to know how are the differences between traditional Islamic education with modern Islamic education. This study uses a historical method where the author collects various primary and secondary sources both archives, books, journals and other relevant sources.The results of this study indicate that Islamic education is education organized by people or Islamic institutions with a system and curriculum based on Islam (Al Quran and As Sunnah). There are special characteristics about the traditional Islamic education system in Indonesia that are different from the modern Islamic education system. These special characteristics can be seen at least from six aspects that consist of place of teaching, teaching methods, curriculum, orientation, management of institutions, and education funding systems.